THE USE OF THREE-DIMENSIONAL VISUALIZATION TOOLS TO DETECT DEFICIENCIES IN GEOMETRIC ROADWAY DESIGNS - FIGUEIRA, AURENICE DA CRUZ; LAROCCA, ANA PAULA C.; QUINTANILHA, JOSÉ ALBERTO; KABBACH JR, FELIPE ISSA (Boletim de Ciências Geodésicas, 2014)
The use of three-dimensional (3D) visualization technologies in the field of transportation sciences has contributed not only to the assessment of the impact of a road project on its surroundings but also to the development and study of elements of the geometric design itself. The present study aimed to assess the effectiveness of the use of 3D visualization tools in the detection of poor compatibility between the horizontal and vertical alignments of a road project. The assessment was performed by conducting tests with groups of participants who were students from a civil engineering course with no experience in the development of geometric roadway designs. These participants each assessed two road stretches: one stretch with unflawed coordination between the vertical and horizontal alignments of the road and another stretch in which this coordination had been intentionally distorted. It was used an application software for roadway geometric designs that allowed the creation of a video of the trajectory of the targeted road. Subsequently, the participants answered a questionnaire that aided the interpretation of the results regarding the design deficiencies in road layouts perceived from the 3D visualization of the roadways.